Surgical Outcomes of Laparoscopic versus Open Inguinal Hernia Repair in Children: A 10-year Single-surgeon Study - Amar Shah; Ria Sharma; Anirudh Shah (Journal of Indian Association of Pediatric Surgeons)
Aims: The aims of this study were to compare surgical outcomes of conventional open inguinal hernia repair (OR) with laparoscopic repair of inguinal hernia (LR) repair in Indian children operated by a single surgeon. Materials and Methods: This is a retrospective (historical) nonrandomized cohort study of 1595 children with unilateral inguinal hernia for 10 years. All children who presented with unilateral inguinal hernia were included in this study. The study was divided into two phases of 5 years each, and patients were classified into Group 1 and Group 2. In the first 5 years (Group 1), all the children with unilateral inguinal hernia underwent conventional open repair. Over the next 5 years (Group 2), all the children with unilateral inguinal hernia underwent laparoscopic repair. All the operations were performed by the same surgeon who was well acquainted with laparoscopic surgery. Parameters studied included gender, side of the hernia, time of surgery, incidence of contralateral patent processus vaginalis (PPV), development of metachronous contralateral hernia, and complications. Results: A total of 1595 children with unilateral inguinal hernia were studied. Nine hundred and forty-five patients underwent OR (Group 1), and 650 patients underwent LR (Group 2). The male-to-female ratio in Group 1 was 2.5:1, and in Group 2 was 2.4:1. Right inguinal hernia was present in 59%, whereas 41% had a left inguinal hernia. In Group 1, 8% of children developed metachronous contralateral hernias. In Group 2, the contralateral processus vaginalis was found to be patent in 260 children. However, only 10% (26) of these children developed metachronous contralateral hernia on follow-up. In the present study, a significantly higher recurrence rate (2.5%) was observed in the LR group as compared to the OR group (0.3%). The overall operative time was lesser in the OR group (15 ± 8.4 min) versus LR group (25 ± 10 min). Conclusions: Only 10% of children with contralateral PPV in our study went on to develop a symptomatic hernia. Hence, we believe that upfront closure of the contralateral PPV with unilateral inguinal hernia may not be necessary. LR has a longer operating time and higher recurrence rates. The choice of technique depends on factors such as the availability of laparoscopic equipment and infrastructure, surgeon’s preference, and expertise.